ChemInform Abstract: Synthesis of Flavokawain B and Its anti‐Proliferative Activity Against Gefitinib‐Resistant Non‐Small Cell Lung Cancer (NSCLC). Issue 18 (17th April 2014) - Seo, Young Ho; Oh, Yong Jin
Abstract: The natural product flavokawain B (I) impairs the growth of gefitinib‐resistant non‐small cell lung cancer (H1975) and disrupted Hsp90 chaperoning function.